Effect of creep-feeding supplementation during the pre-weaning phase on gene co-expression in Longissimus thoracis muscle of F1 Angus x Nellore calves at weaning - Henrique Gonçalves Reolon; João Pedro Martins Borges; Gabriel Luiz Navarro Liberal; Germán Darío Ramirez-Zamudio; Guilherme Luis Pereira; Juliana Akamine Torrecilhas; Welder Angelo Baldassini; Marcos Eli Buzanskas; Otávio Rodrigues Machado Neto; Luis Artur Loyola Chardulo; Rogério Abdallah Curi (PLoS ONE, 2025)
The aim of this study was to analyze gene co-expression in skeletal muscle of calves with or without creep-feeding during the pre-weaning phase. Forty-eight F1 uncastrated male Angus-Nellore calves were divided into two groups: G1 - no creep-feeding, and G2 - creep-feeding. After weaning (210 days), all animals were kept in the feedlot for 180 days under the same conditions. Weaning weight, backfat thickness, and intramuscular fat content were significantly higher in G2, with intramuscular fat and marbling score being 17.2% and 14.0% higher, respectively, compared with G1 (P < 0.05). Longissimus thoracis muscle samples were collected at weaning for transcriptome analysis (RNA-Seq) in 12 animals of each group. Gene co-expression analysis using the CEMiTool R package identified seven modules; five showed differential activity between groups (adjusted P < 0.002). Modules 1, 2, and 3 showed the greatest association with treatments. Hub genes and enrichment in biological pathways and processes were identified in these modules. The absence of supplementation was associated with increased connectivity of hub genes involved in insulin signaling, oxidative metabolism, and cell cycle regulation, including CDKN1A , FOXO1 , and NAMPT . These genes were enriched in processes related to lipid oxidation and response to ketone bodies, suggesting reduced myogenic and adipogenic activity. Notably, FOXO1 has context-dependent effects on adipogenesis, acting as both an inducer and inhibitor depending on the differentiation stage. In contrast, supplementation increased the activity of hub genes involved in cell signaling, muscle development, and differentiation, such as ITGB6 , REEP1 , TPCN1 , PPARA , PTPN11 , and MAP3K20 , and enriched processes associated with muscle and adipose cell development. In conclusion, creep-feeding supplementation during the pre-weaning phase altered gene co-expression in skeletal muscle, activating pathways related to myogenesis, adipogenesis, and energy metabolism. These results suggest potential lasting molecular effects consistent with increased intramuscular fat deposition during finishing.